The influence of Cow Manure and Liquid Organic fertilizer Super Natural Nutrition towart growth and yield of land cress (Ipomoea reptans Poir). - Nova Iswanto, Puji Astuti, Zuhdi Y . (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2017)
This experience aims to result the influence of cow manure and liquid organic fertilizer Super Natural  Nutrition as well as their interaction and the resulting growth of land cress plant and obtain dosage of the cow manure and concentration of liquid organic fertilizer super natural nutrition is right to land cress plant.The research was carried out for two months, from late Maret 2016 to Mei 2016. From land preparation until crops.The location of the research in Mekar Jaya village, Sebulu Subdistric and Kutai Kartanegara regency, East Kalimantan Province.Experiment design using a factorial 4 x 4 in a random design group (RAK), with consists of two factors experiment and three group. The first factors is the cow manure (P)this research consists of 4 levels : without cow manure or control (p0), 5 ton/ha cow manureis equel to320 g/plot (p1), 10 ton/ha cow manure is equel to640 g/plot (p2), and 15ton/ha cow manure is equel to960 g/plot (p3). The second factors is the consentration of liquid organic fertilizer super natural nutrition (N) consists of 4 levels : without liquid organic fertilizer super natural nutrition(n0), the consentration of liquid organic fertilizer Super Natural Nutrition 1 ml/l.water (n1), consentration of liquid organic fertilizer Super Natural Nutrition 2 ml/l.water (n2) and then consentration of liquid organic fertilizer Super Natural Nutrition 3 ml/l.water (n3).The result showed that cow manure treatment (P) is significant effect plant height at 10 days after planting. The very significant effect plant height age at 20 days and 30 days after planting. Number of tilers for hill and weight of the crop per plant. The highest treatment  weight of the crop per plant is p3 (dosage cow manure 15 ton/ha equel 960 g/plot) is 69,32 g/plant and the lowest weight of the fresh plant in the treatment of p0 without cow manure or control is 40,00 g/plant.Treatment of liquid organic fertilizer Super Natural Nutrition (N) does not significant effect with number of tilers for hill. The Significanlyt effect plant height at 10 days after planting.Very significantly effect plant height at 20 days and 30 days after planting and weight of the crop per plant.The highest treatment  weight of the crop per plant is n3 (concentration Super Natural Nutrition 3 ml/l.water) is 65,25 g/plant and then The lowest treatment weight of the crop per plant p0 (control treatment), yaitu 46,70 g/plant.The treatment interaction (PxN) does not significantly effectwith plant height age at 10 days, 20 days and30 days after planting andnumber of tilers for hill. Very significant effect with weight of the crop per plant.The highest treatment  weight of the crop per plant is p3n3 (dosage cow manure 15 ton/ha andconcentration pupuk organik cair Super Natural Nutrition 3 ml/l.water) is 99,93 g/plant, and then the lowest treatment weight of the crop per plant p0n0 (control treatment) is 35,20 g/plant.